A spatial exploratory model of rural land prices - Joost Buurman (European Regional Science Association (ERSA), 2001)
The land market in the Netherlands seems to get much attention the last few years. Increasing land use pressure caused by a high population density and an increasing economic growth and prosperity result in competing land use claims from a range of sectors. Strict planning schemes segment the land market into sub markets and create an artificial scarcity of land for some land use types, which results in large price differences between the segments. Decisions of the government for designating housing areas, creating nature areas and expanding infrastructure aim at optimal land use with the least negative externalities, but result sometimes in speculation or unwanted situations on the land market. Additionally, the impact of European policies on the land market is still increasing. This raises discussions on the functioning of the land market. In order to get a better understanding of the land market, this study aims at developing a GIS-based explanatory model for rural land prices. Factors that affect rural land prices are collected, analysed, categorised, and used to explain spatial differences in prices of parcels of land in rural areas. Special attention is paid to modelling the effect of governmental policies like zoning and taxing can be analysed with the model. The current model is based on data for the province of Noord-Brabant in the southern part of the Netherlands. For this province data on parcel level is available. Using a geographical information system (GIS) this data can be combined with a rich set of spatial data. The resulting model can be used to carry out case studies like studying the effect of relocation of farmers or the effect of land purchases by the government.
Keywords: 330